Change of serum prealbumin levels and serum protein markers between egg white powder and casein protein additives in standard enteral feeding formulas in critically ill patients with acute respiratory failure. Issue 1 (December 2016) - Bhurayanontachai, Rungsun; Sa-nguansai, Sunatee
Abstract Background Protein deficiency is a major problem in critically ill patients. Egg white powder recently became a standard additive for protein supplementation in our unit. However, clinical data are not available to support egg white powder supplementation compared to standard protein casein supplementation. This study aimed to determine the change of serum prealbumin (PAB) levels of egg white powder compared to casein additive in standard enteral feeding in critically ill patients with respiratory failure. Methods A prospective double-blind, randomized, non-inferiority study was conducted in patients with acute respiratory failure in the medical intensive care unit and respiratory care unit. These patients randomly received 1500 kcal/day of enteral nutrition support with 40 g/day of protein additives by either egg white protein powder or casein protein for 7 days. The serum PAB and C-reactive protein (CRP) levels were measured on days 1, 3, 5, and 7. Repeated-measures ANOVA determined the group effects displayed by serum PAB and CRP levels.p values <0.05 were considered statistically significant. Results Thirty-four patients were in two groups: 17 in the casein protein group and 17 in the egg white powder group. The clinical characteristics, baseline nutritional status, and biochemistries were not significantly different between the groups. No statistically significant differences were seen in the serum PAB and serum CRP levels between the two groups. The average mean ± SEM difference of serum PAB level between the groups was 2.3 ± 2.5 mg% (p = 0.58). Conclusions The levels of PAB between the egg white protein additive and casein protein additive were not significantly different and less than the non-inferior margin. Trial registration Thai Clinical Trials RegistryTCTR20160126002